Improvement of surface properties of fiber-reinforced polymer composites by metallization strategies: Technologies, challenges and prospects - Xuan Su; Junyi Gu; Yan Diao; Yingke Wang; Jie Xu; Bin Guo (Journal of Materials Research and Technology)
Surface metallization is an effective method to improve the surface hardness and conductivity of fiber-reinforced polymer (FRP) and enhance their high-temperature performance. This article provides a literature review on the preparation of metal coatings on FRP surfaces. A review was conducted on the latest research progress of thermal spraying, cold spraying, and laser cladding technologies, including coating deposition principles and processes, and coating formation characteristics. Detailed discussions were conducted on various FRP surface pretreatment techniques, including sandblasting, laser texturing, plasma treatment, and corresponding Interface adhesion enhancement mechanism. In addition, the performance improvement brought by surface metallization of FRP and the engineering application requirements were also discussed. Finally, various metallization technologies were compared in terms of material characteristics, process features, advantages and disadvantages, and development directions were discussed.